Deformation and Damping Characteristics of Lightweight Clay-EPS Soil under Cyclic Loading - Yundong Zhou; Mingdong Li; Qibao He; Kejun Wen (Advances in Civil Engineering)
Lightweight Clay-EPS Soil (LCES) is a newly developed material which has many merits such as the adjustability of strength and density, simplicity for construction, and economical efficiency. It has been widely applied in practical engineering, e.g., soft ground improvement, the solvent of bridge head jump, earthfill of pipeline, and broadening of highway. Meanwhile, construction castoff and industrial waste can be recycled as a major ingredient in LCES. The dynamic deformation characteristics of LCES and clay were comprehensively studied using laboratory dynamic triaxial tests. It was found that the compressive strain of LCES increased while the growth rate of strain decreased with the increasing number of cycles, which conformed to a hyperbola model. The dynamic secant elastic modulus of LCES decreased with the increase of dynamic strain, which was represented by strain softening. The dynamic modulus of clay decreased sharply, while that of LCES decreased marginally. Moreover, the damping ratio of LCES tended to increase with the increasing dynamic strain. The damping ratio of LCES was lower than that of clay at the same strain level. It was also found that cement content had a negative relationship with the damping ratio of LCES, while the effect of EPS beads content was adverse. The damping ratio of both LCES and clay decreased moderately.